Development of Automated System Data Collection of Traffic Control at Intersections and Violation Analysis Software Complex (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Automation of traffic control at intersections to reduce traffic congestion and video images of traffic at the studied intersection were analyzed using a computer vision tool that extracts traffic flow data. However, most of these studies did not consider the systematic integration of traffic data collection methods in optimal signal timing control. This study developed a three-part system to create an optimized variable cctv time mode regulated by fixed-time road cctv cameras for a traffic congested intersection. The data underwent a further data collection process, resulting in an accuracy of more than 90%. The final dataset was then analyzed by a local transport expert.